Winds of change the environmental movement and the global development of the wind energy industry - Vasi, Ion Bogdan (New York ; Oxford : Oxford University Press, 2011)
'Winds of Change' examines the global development of the wind energy industry from a political, social movements-based perspective. It shows the varying influence that the environmental movement has had on the growth of this industry in different countries and regions, and the different outcomes this varying influence has led to.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 21, 2010).
Keywords: Wind power industry; Environmentalism